ANALYSIS OF SAND DUNES DAMAGES USING REMOTE SENSING METHOD IN PARANGTRITIS KRETEK BANTUL - Wenang Anurogo; Muhammad Zainuddin Lubis; Eni Heldayani (JURNAL SWARNABHUMI : Jurnal Geografi dan Pembelajaran Geografi, 2017)
ABSTRAKIndonesia passed the equator make Indonesia get some kind of wind. The wind helps the formation ofsand dunes such as those on parangtritis. Human population is growing and is not supported by theincrease of the land, then the existence of sand dunes began to interfere with land transfer function for thefulfillment of human needs. The purpose of this research is to determine the extent of damage andreduction of the sand dune area in parangtritis and the cause of its damage. The method used in thisresearch is the extraction of information from spatial data in each year of data recording then analyzed toobtain data or information regarding changes in sand dunes area. The interpretation results show that thearea of sand dunes in 2003 was 277,083 Ha, while the area of sand dunes with visual interpretation of theimage of 2015 shows that the current sand dune area is 169.378 Ha. The results of both areas of the sanddunes experienced a reduction of 107,705 hectares or it can be said that the sand dunes area over the yearspan experienced a reduction of 47.4%.Key Word: Sand dunes; Spatial Data; Land Transfer Function.